Influence of stationary and bioreactor cultivation on Lentinula edodes (berk) pegler lignocellulolitic activity - Regina,Magali (2008)
This work aimed to study the stationary and periodically mixed culture of L. edodes to the production of lignocellulolitic enzymes activity. LE 95/17, LE 96/22 and Leax strains were incubated in 25 g of eucalyptus sawdust substrate in Erlenmeyer flasks in stationary culture at 25º C and in a bioreactor with four complete rotations daily at 25º C and 3% CO2. The samples were collected at 8, 11, 14, 17 and 20 days after the incubation. Oxidative and hydrolytic enzymes analyses were performed. Lignin peroxidase enzyme was not found in the lignolytic system for LE 95/17, LE 96/22 and Leax strains in the different incubation methods. The use of bioreactor could be a practicable system to induce the laccase activity for L22 and Leax and MnP activity for L17 and L22. The activity of the hydrolytic enzymes was higher in the stationary system in comparison to periodically mixed system in the bioreactor.